Reception/Bevakning/Kritik - Örjan Torell; Mattias Pirholt; Anders Pettersson; Mats Jansson; Jesper Olsson; Janina Orlov; Hanne-Lore Andersson (Tidskrift för Litteraturvetenskap, 2008)
Örjan Torell om Magnus Persson, Varför läsa litteratur?